STUDI TERKAIT DENGAN DEWAN KOMISARIS DAN KUALITAS LAPORAN KEUANGAN SERTA DAMPAKNYA TERHADAP ASIMETRI INFORMASI - Albert Tampubolon; Hisar Pangaribuan (Jurnal Ekonomis, 2019)
This study aims to determine the effect of independent board of commissioner on financial report quality, to find out the effect of size of board commissioner on financial report quality, to find out the effect of financial report quality on asymmetry information, to find out the effect of financial report quality as a intervening variable for independent board of commissioner and asymmetry information, and to find out the effect of financial report quality as intervening variable for size of board of commissioner and asymmetry information. This study used partial least square/ variance based statistic method. The result from this study found out that Board of Commissioner can’t directly impact on financial report quality. Excellent financial reporting as well as high quality of financial report raised the quality and relevancy of information to users, further reduced asymmetry information. The other result implied to future study need to involve the audit committee as intervening variable on financial report quality.